On the true antiquity of Eoarchean chemofossils – assessing the claim for Earth's oldest biogenic graphite in the Saglek Block of Labrador - Whitehouse, M.; Dunkley, Daniel; Kusiak, M.; Wilde, Simon (Elsevier BV, 2019)
A recent claim to have found traces of Earth's earliest life (>3.95 Ga) utilising isotopically light carbon in graphite-bearing metapelites from the Saglek Block of northern Labrador, Canada, is re-evaluated applying rigorous geological and geochronological criteria. The establishment of these criteria in previous evaluations of early life claims from southern West Greenland and northern Canada is reviewed in order to provide a backdrop to discussion of the Saglek claim. In particular, we emphasise the importance of the scale of lithological continuity in determining the veracity of such claims, which are considerably easier to demonstrate from large, relatively less tectonised supracrustal remnants like the Isua Greenstone Belt than they are from smaller, isolated enclaves of the kind found on Akilia or the highly tectonised and imbricated unit that is found in the Saglek Block. Unambiguous field relationships between ca. 3.9 Ga tonalitic gneiss and the graphite-bearing metasediments have not been demonstrated in the literature that the Saglek claim relies upon, and earlier U-Pb-Hf isotopic studies on zircon from metasediments at one of the localities used in the claim indicate a Mesoarchean to Neoarchean time of deposition. We conclude that, irrespective of the validity of the carbon isotopic evidence, field relationships and geochronological evidence fail to demonstrate an age of >3.95 Ga for the potential traces of life.